Effects of Dosage of Mix.Microorganisms in Feed Raw Materials Fermentation Containing Sargassum sp. on Growth Performance, Chemical Body Composition and Hepatosomatic Index of Milkfish, Chanos chanos Forsskal - Aslamyah, Siti; Karim, Muh. Yusri; Badraeni, Badraeni (Torani Journal of Fisheries and Marine Science, 2018)
Mixed microorganisms consist of bacteria, fungi, yeasts, and molds that produce important enzymes to ferment raw materials, thereby increasing the nutrient content of milkfish feed. This study aims to examine various doses of mix. microorganisms fermented raw materials on growth performance, chemical composition of the body, and hepatosomatic index of milkfish. Milkfish weighing 28.40 ± 0.11 g is kept in hapa of 1 m3 and placed on brackish water ponds. The test feed contains Sargassum sp. and formulated from raw materials fermented with mix. microorganism (control, 10, 15 and 20 mL / 100 g). The experimental results show the relative growth rate (%) and the growth of biomass (g) of milkfish fed with fermented feedstock with a dose of 10 mL / 100 g (122.77 ± 3.00%, and 522.05 ± 12.19 g ), the real feed is higher than the other dose. The fat content, crude fiber, and energy of test fish fed with fermented feedstock with 10, 15, and 20 mL / 100 g doses were significantly lower, while the hepatosomatic index was significantly higher than the control. (91.11-97,78%), protein content and NFE or Nitrogen Free Extracts (66.81 ± 0.41 72.33 ± 0.28% and 0.88 ± 0.38- 2.24 ± 0.92%), hepatic and muscle glycogen (7.16 ± 0.25-7.3 ± 0.31 mg / g and 6.16 ± 0.16, 6.51 ± 0.35 mg / g) were the same in all treatments. Thus, a dose of 10 mL / 100 g feed ingredients is the best dose in fermenting feed ingredients.Keywords: fermentation,  milkfish,  mix. microorganism, artificial feed, Sargassum sp.